PEMAKAIAN BAHASA DALAM ACARA DEBAT CALON PRESIDEN DAN WAKIL PRESIDEN TAHUN 2014 DI METRO TV - Rohmad Miftah Jati Nugroho; Basuki Basuki (Universitas Sarjanawiyata Tamansiswa, 2017)
This study aims (1) to describe forms of language use on debating program of president and representative president candidate 2014, Metro TV, (2) factors that influence the different use of language on debating program of the president and representative president candidate 2014, Metro TV. This study belongs to descriptive qualitative research. Data resource in this research was the language used on the second and third cycle of debating program of president and representative president candidate 2014 that have been broadcasted byÂ Metro TV. Data collection methods in this research were simak method with simak bebas libat cakap technique, recording technique, and writing technique. Data analysis methods that used in this research were agih method with contrast and opposition technique as its analysis technique. Data results of this research were (1) forms of language use on debating program of president and representative president candidate 2014, Metro TV consists of (a) phonological variation such as suffix change and monoftongisasi, (b) morphological variation like omission and deletion of prefix in several utterances that uttered when debating program of president and representative president candidate 2014 being conducted, (c) lexicon variation such code-mixing between foreign language and Bahasa Indonesia and then code-mixing between some Javanese utterances and Bahasa Indonesia (2) factors that influence the different use of language on debating program of president and representative president candidate 2014, Metro TV which consists of (a) setting and scene, (b) participants, (c) ends, (d) act sequence, (e) norm of interaction and interpretation, (f) genre.